The Poetic Works of Helius Eobanus Hessus : Volume 6: The Fruits of Autumn, 1528-1539 - Vredeveld, Harry (Early Modern History and Modern History E-Books Online, Collection 2025., 2025)
This cornucopia of poetic fruits from Hessus's autumn opens with "On the Tumults of These Times" (1528), meditating on the Peasant War and the Sack of Rome, and exhortations to Emperor Charles V to heal Germany's traumas and defeat the Turks (1530). Next are the masterpieces, "Epicedia" (1531), mourning famous contemporaries; the urban praise "Nuremberg Illuminated" (1532); and three books of Christian "Heroides" (1532), updated to reflect Lutheran teaching. The collection concludes with three dirges, a panegyric of Landgrave Philip's victory in Württemberg (1534), an "Elegy on Slander" for Melanchthon (1538), and an "Epithalamion" for the Marburg jurist Justus Studaeus (1539).